Development of reference material with assigned value for human T‐cell leukemia virus type 1 quantitative PCR in Japan. (21st October 2018) - Kuramitsu, Madoka; Okuma, Kazu; Nakashima, Makoto; Sato, Tomoo; Sasaki, Daisuke; Hasegawa, Hiroo; Umeki, Kazumi; Kubota, Ryuji; Sasada, Keiko; Sobata, Rieko; Matsumoto, Chieko; Kaneko, Noriaki; et al.
ABSTRACT: Quantitative PCR (qPCR) of human T‐cell leukemia virus type 1 (HTLV‐1) provirus is used for HTLV‐1 testing and for assessment of risk of HTLV‐1‐related diseases. In this study, a reference material was developed for standardizing HTLV‐1 qPCR. Freeze‐dried TL‐Om1 cells diluted with Jurkat cells were prepared and an assigned value for proviral load (PVL) of 2.71 copies/100 cells was determined by digital PCR. Nine Japanese laboratories using their own methods evaluated the PVLs of this reference material as 1.08–3.49 copies/100 cells. The maximum difference between laboratories was 3.2‐fold. Correcting measured PVLs by using a formula incorporating the assigned value of this reference material should minimize such discrepancies.